Continuity Of Care For Postpartum Mothers With Breastfeeding Problems At Puskesmas Batealit Jepara - Ardiana Umi Kulsum; Putri Rahma Dini; Arri Miosa (Journal for Quality in Public Health, 2023)
Continuity of care (COC) midwifery care is one way to be able to provide care and carry out continuous documentation to reduce complications that occur, besides that this care is reviewed from the postpartum period which is carried out continuously and continuously. The purpose of the study is to apply midwifery care management to mothers in continuity of care (COC). Method; Type of descriptive research case study method conducted on 6 respondents who are different from puerperal cases. The results of pregnancy care are carried out according to the standards of care for the last postpartum visit, intervention is carried out according to existing complaints, namely with cabbage leaf compresses. The results that have been obtained by the patient feel that the milk comes out smoothly and does not look tense and full. The results of COC midwifery care are able to overcome the problem of breast milk that is not smooth with the use of materials at home